2005
DOI: 10.1177/030089160509100613
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers and Prognosis in Locally Advanced Breast Cancer

Abstract: Background Locally advanced breast cancer (LABC) represents a heterogeneous subgroup of breast cancer with an often dismal outcome. Identifying prognostic factors has acquired great significance for the selection of optimal treatment in individual patients. Methods Between January 1993 and December 1997, 103 patients were treated in our institution with multimodality treatment consisting of neoadjuvant chemotherapy followed by surgery, adjuvant chemotherapy and radiotherapy; tamoxifen was added in hormone rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
6
2
Order By: Relevance
“…The results of serum CA15.3 revealed no significant change compared to normal in all the studied groups and this agree with previous studies that emphasized that the most important application of CA15.3 is in predicting outcome and monitoring therapy in patients with advanced breast cancer [23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…The results of serum CA15.3 revealed no significant change compared to normal in all the studied groups and this agree with previous studies that emphasized that the most important application of CA15.3 is in predicting outcome and monitoring therapy in patients with advanced breast cancer [23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, not all studies agreed on the same set of risk factors explaining variation in prognosis following breast cancer metastasis [29]. Some studies have shown that age, number of metastatic sites, ER/PR and HER2 status, ECOG-PS and baseline values of CEA and CA15-3 are valuable prognostic factors [28,29,30,31]. Nevertheless, our study did not provide support for a signi cant in uence of any of these factors on survival in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 67%
“…Notably, not every study identifies the same set of risk factors explaining variation in prognosis following breast cancer metastasis (26). Some studies have shown that age, number of metastatic sites, ER/PR and HER2 status, ECOG-PS and baseline values of CEA and CA15-3 are valuable prognostic factors (25,26,27,28). Nevertheless, our study did not provide support for a significant influence of any of these factors on survival in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 64%